PERFORATION AND PENETRATION OF FIBER METAL LAMINATES TARGET BY HEMISPHERICAL PROJECTILE - Fadly, Muhammad Syaiful; Purnowidodo, Anindito; Setyarini, Putu Hadi; Bakri, Bakri; Chandrabakty, Sri (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
This study aims to examine the phenomena that occur due to projectile penetration on fiber metal laminate. Ballistic testing was carried out experimentally according to National Institute of Justice standards (NIJ Standard 0101.06 level III-A) using a 9 mm full-metal jacket projectile with a normal angle of attack (90° to the target). The results showed that fiber metal laminate could withstand the projectile rate by penetrating the first layer (aluminum plate) and the second layer (aramid/epoxy), while the last layer was deformed to form a bulge. The pierced aluminum plate is characterized by petalling failure. Meanwhile, the aramid/epoxy was penetrated by the projectile with failure of the primary yarn to break the fiber.